Plant Conservation Practitioners Can Benefit from Neutral Genetic Diversity - Mi Yoon Chung; Sungwon Son; Jordi López-Pujol; Kangshan Mao; Myong Gi Chung (Diversity, 2021)
Several papers deal with a conservation genetics gap in which plant conservation and restoration managers or practitioners do not soundly integrate population genetics information into conservation management. Authors concerned about this issue point out that practitioners perceive genetic research results to be impractical or unnecessary in the short term due to time and financial constraints. In addition, researchers often fail to translate research findings into comprehensive, jargon-free recommendations effectively. If possible, conservation-related or conservation-oriented articles should be easily written to bridge the research–implementation gap. Finally, based on a previously published prioritization framework for conservation genetics scenarios, we introduce four simple genetic categories by exemplifying each case. We hope that conservation practitioners could employ these suggested guidelines for the prioritization of population- and species-level management.